Understanding Compliance Dynamics in Community Justice Settings: The Relevance of Bourdieu’s Habitus, Field, and Capital - Ugwudike, Pamela (International criminal justice review, 2017)
This article seeks to expand the existing literature on compliance in community justice settings by highlighting the importance of service user participation in efforts to achieve compliance. The article’s central argument is that although co-productive strategies can enhance service user participation, the degree to which co-production is achievable in penal supervision is perhaps uncertain, and has received insufficient theoretical or empirical attention. To address the gap in knowledge, the article draws on the data generated from a study of compliance in Wales, United Kingdom, and employs the Bourdieusian concepts of habitus, field, and capital to argue that the convergence of two key factors undermines the viability of co-productive strategies in penal settings. One factor is the service users’ habitus of powerlessness which may breed passivity rather than active participation. The second also relates to the power dynamics that characterize penal supervision contexts. Within these contexts, practitioners are statutorily empowered to implement and enforce the requirements of community orders. In the current target-focused policy climate in England and Wales, practitioners may prioritize measurable compliance over forms of compliance that stem from service user participation and engagement perhaps because these are not readily quantifiable.